2020
DOI: 10.1590/1980-57642020dn14-030013
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in patients with Myasthenia Gravis: an association with glucocorticosteroid use and depression

Abstract: ABSTRACT. We investigated the cognitive performance of patients with Myasthenia Gravis (MG) through a cross-sectional study. A battery of cognitive assessments and self-report questionnaires regarding quality of life (QoL), sleep, and depression were applied. The sample consisted of 39 patients diagnosed with MG. The scores showed a predominance of cognitive impairment in the Montreal Cognitive Assessment screening test (MoCA) (66.7%) and in the immediate (59.0%) and recent memory (56.4%) tests. However, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(51 reference statements)
1
3
1
Order By: Relevance
“…As far as is known, this study is the first that has been purposefully designed to evaluate the frequency of MCI in MG; therefore, comparison with other data is not feasible. However, in a recent Portuguese study, the authors using the Montreal Cognitive Assessment (MoCA)a first-level screening test for MCI-described a frequency of cognitive impairment of 66.7%, which is rather similar to that described in the present study [10].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…As far as is known, this study is the first that has been purposefully designed to evaluate the frequency of MCI in MG; therefore, comparison with other data is not feasible. However, in a recent Portuguese study, the authors using the Montreal Cognitive Assessment (MoCA)a first-level screening test for MCI-described a frequency of cognitive impairment of 66.7%, which is rather similar to that described in the present study [10].…”
Section: Discussionsupporting
confidence: 85%
“…Some authors showed that corticosteroids may induce negative effects on memory and executive functioning [40]. Indeed, in a cross-sectional study conducted by Ayres and colleagues, the authors described an association between worse memory performance, depression, and glucocorticoid use [10]. Although no association was found between cognitive impairment and corticosteroid use in the present study, we found a positive correlation between BDI score and prednisone dosage.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…However, prednisone does have an effect on CNS function. The use of glucocorticosteroids can alter cognition and mood (30,31). We took the effects of hormones on cognition into account but did not perform the subgroup, correlation, and IRM, immediate recall memory; DRM, delayed recall memory; LL, lower limit; UL, upper limit; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%